Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawani - Khoirunnisa, Afina; Arnu, Anggi Pasca (Jurnal Ilmiah Wahana Pendidikan, 2024)
In a corporate institution or organization work environment and work discipline is very important to know if there is a significant influence on the performance of employees, therefore this researcher aims to determine and assess the influence of the work environment and work discipline on employee performance. This research is included in the qualitative descriptive research that uses library sources, especially the examination and interpection of previous research on the influence of the work environment and work discipline on employee performance, the analysis of library research results that there is an influence between the work environment on employee performance and work discipline on employee performancei